Functional Characterization of the GUCY1A3 Coronary Artery Disease Risk Locus. Issue 5 (1st August 2017) - Kessler, Thorsten; Wobst, Jana; Wolf, Bernhard; Eckhold, Juliane; Vilne, Baiba; Hollstein, Ronja; von Ameln, Simon; Dang, Tan An; Sager, Hendrik B.; Moritz Rumpf, Philipp; Aherrahrou, Redouane; Kastrati, Adnan; et al.
Abstract : Background: A chromosomal locus at 4q32.1 has been genome-wide significantly associated with coronary artery disease risk. The locus encompasses GUCY1A3, which encodes the α1 subunit of the soluble guanylyl cyclase (sGC), a key enzyme in the nitric oxide/cGMP signaling pathway. The mechanism linking common variants in this region with coronary risk is not known. Methods: Gene expression and protein expression were analyzed with quantitative polymerase chain reaction and immunoblotting, respectively. Putative allele-specific transcription factors were identified with in silico analyses and validated via allele-specific quantification of antibody-precipitated chromatin fractions. Regulatory properties of the lead risk variant region were analyzed with reporter gene assays. To assess the effect of zinc finger E box-binding homeobox 1 transcription factor (ZEB1), siRNA-mediated knockdown and overexpression experiments were performed. Association of GUCY1A3 genotype and cellular phenotypes was analyzed with vascular smooth muscle cell migration assays and platelet aggregation analyses. Results: Whole-blood GUCY1A3 mRNA levels were significantly lower in individuals homozygous for the lead (rs7692387) risk variant. Likewise, reporter gene assays demonstrated significantly lower GUCY1A3 promoter activity for constructs carrying this allele. In silico analyses located a DNase I hypersensitivity site to rs7692387 and predicted binding of the transcription factor ZEB1 rather to the nonrisk allele, which was confirmed experimentally. Knockdown of ZEB1 resulted in more profound reduction of nonrisk allele promoter activity and a significant reduction of endogenous GUCY1A3 expression. Ex vivo–studied platelets from homozygous nonrisk allele carriers displayed enhanced inhibition of ADP-induced platelet aggregation by the nitric oxide donor sodium nitroprusside and the phosphodiesterase 5 inhibitor sildenafil compared with homozygous risk allele carriers. Moreover, pharmacological stimulation of sGC led to reduced migration only in vascular smooth muscle cells homozygous for the nonrisk allele. In the Hybrid Mouse Diversity Panel, higher levels of GUCY1A3 expression correlated with less atherosclerosis in the aorta. Conclusions: Rs7692387 is located in an intronic site that modulates GUCY1A3 promoter activity. The transcription factor ZEB1 binds preferentially to the nonrisk allele, leading to an increase in GUCY1A3 expression, higher sGC levels, and higher sGC activity after stimulation. Finally, human and mouse data link augmented sGC expression to lower risk of atherosclerosis. Abstract : Supplemental Digital Content is available in the text.